The effect of macroeconomic variables and the global financial crisis on Indonesia's Sharia stosk index during 2008 - 2021 - Dhony Kalinggajati (Program Pascasarjana Universitas Islam Negeri Sunan Kalijaga, 2023)
et,1/adil,c.1